1992
DOI: 10.21273/hortsci.27.5.411
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Enhances the Effectiveness of Ethephon on Anthocyanin Production in Cranberry Fruits in the Field

Abstract: The application of ethanol for enhancing effectiveness of ethephon under field conditions on cranberry (Vaccinium macrocarpon Ait.) fruit was tested during three seasons (1986 to 1988). The formulation containing ethephon plus the surfactant Tergitol (0.3% or 0.5%, v/v) and ethanol (2.5%, 5%, or 10%) consistently increased anthocyanin content in the fruit by 28% to 54% over the control. In general, fruit size was not affected by the ethephon treatment containing ethanol and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
(1 reference statement)
2
8
0
Order By: Relevance
“…However, such leakage of electrolytes was significantly reduced when the fruits were pretreated by the growth regulators, used in this study, especially LPE at 200 or 400 ppm in addition to the treatments of putrescine at 1 or 2 mM. The significant reduction in the leakage of cold stored olives that were treated by LPE could be attributed to its ability to delay tissue senescence, repair the plasma membrane damage and inhibit the activity of phospholipase D (the destructive enzyme) as reported by (Farag et al, 1992;Ozgen et al, 1999).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, such leakage of electrolytes was significantly reduced when the fruits were pretreated by the growth regulators, used in this study, especially LPE at 200 or 400 ppm in addition to the treatments of putrescine at 1 or 2 mM. The significant reduction in the leakage of cold stored olives that were treated by LPE could be attributed to its ability to delay tissue senescence, repair the plasma membrane damage and inhibit the activity of phospholipase D (the destructive enzyme) as reported by (Farag et al, 1992;Ozgen et al, 1999).…”
Section: Discussionsupporting
confidence: 71%
“…It has been reported that pitting of fruit tissues, browning and shriveling are the main symptoms of chilling injury (Farag et al, 1992;Farag et al, 2005;Golding, 2019). Thus the breakdown of sub-surface fruit tissues and their collapse results such pitting.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Beaulieu and Saltveit (1997) have shown that low doses of ethanol could stimulate early fruit ripening while high doses inhibit it. Ethanol has also been found to amplify the effect of ethephon, a commercially available growth regulator, on berry coloration (Farag et al, 1992). Other studies have shown that methanol can also enhance berry anthocyanin content (Nikolaos et al, 2003) and fruit quality (Ramadan and Omran, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…The application of exogenous ethanol has been reported to inhibit or promote tomato fruit ripening in a dose-dependent manner, correlated to ethylene evolution [1]. Farag et al [2] showed that ethanol in combination with an ethylene precursor enhanced anthocyanin content of cranberries. In a recent study [3], we observed that spraying an aqueous solution of ethanol onto grapes at veraison enhanced internal ethylene production.…”
Section: Introductionmentioning
confidence: 99%